Negotiating the Canon: Arab Women Romantic Poets Jamila al-ʿAlayli and Zahra al-Hurr - Amer, Osama (AUC Knowledge Fountain, 2025)
This thesis examines the engagement of two Arab romantic women poets, Jamila al-ʿAlayli and Zahra al-Hurr, with the Arabic literary canon, focusing on how they negotiated their positions within the canon. Despite being active contributors to the Arabic romantic movement, their works remain overlooked in literary histories and anthologies. The study explores the modes of canonization, such as gender essentialism, exceptionalism, and socio-political engagement, by which the canon operates. Through a feminist lens, this research analyzes selected poems, autobiographical texts, articles, interviews, and critical writings by both poets, highlighting their distinct strategies for challenging and reshaping their literary status. Al-ʿAlayli emphasized women's innate romantic sensibility and positioned herself within the male-dominated Apollo literary circle, while al-Hurr employed her exceptional status and connected with her socio-political context. This thesis seeks to expand the understanding of Arabic romanticism by critically engaging with their works and reception.